Experimental determination of the temperature in a small neighborhood of the gas infrared sources; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Kuznetsov G. V. Geny Vladimirovich; Kurilenko N. I.; Mamontov G. Ya. Gennady Yakovlevich; Mikhailova L. Yu. (2015, 2015)
Title screen